Aurantio-obtusin relaxes systemic arteries through endothelial PI3K/AKT/eNOS-dependent signaling pathway in rats - Shuzhen Li; Qian Li; Xinyu Lv; Lin Liao; Weiwei Yang; Shanshan Li; Ping Lu; Daling Zhu (Elsevier, 2015)
Aurantio-obtusin is a natural effective compound isolated from Semen Cassiae, which possesses hypotensive and hypolipidemic effects. Although its hypotensive effect have been clarified, mechanisms Aurantio-obtusin relaxes systemic arteries remain unclear. This study was to investigate effects and mechanisms of Aurantio-obtusin on isolated mesenteric arteries (MAs). We examined MAs relaxation induced by Aurantio-obtusin on rat isolated MAs, expression and activity of endothelial nitric oxide synthase (eNOS) and protein kinase B (AKT), and nitric oxide (NO) production in bovine artery endothelial cells (BAECs). Findings showed Aurantio-obtusin elicited dose-dependent vasorelaxation with phenylephrine (PE) precontracted rat MA rings (diameter: 200-300 μm), which can be diminished by denudation of endothelium and inhibition of eNOS activity, while having no effect on rat isolated pulmonary artery (PA) rings. Aurantio-obtusin increased NO production by promoting phosphorylations of eNOS at Ser-1177 and Thr-495 in endothelial cells. Aurantio-obtusin also promoted phosphorylations of Akt at Ser-473. PI3K inhibitor LY290042 could diminish vasorelaxation induced by Aurantio-obtusin. Moreover Aurantio-obtusin also elicited dose-dependent vasorelaxation effect with PE precontracted MA rings (diameter: 100-150 μm). Therefore, vasorelaxation induced by Aurantio-obtusin was dependent on endothelium integrity and NO production, which mediated by endothelial PI3K/Akt/eNOS pathway. Results suggest Aurantio-obtusin may offer therapeutic effects in hypertension, as a new potential vasodilator.